PENDIDIKAN INKLUSIF DI TINGKAT SEKOLAH DASAR: KONSEP, IMPLEMENTASI, DAN STRATEGI - Erni Murniarti; Nouf Zahrah Anastasia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2016)
In 1994, it has been set Salamanca Statement and Framework for Action on Special Needs Education which contains about the importance of Education for all including education for children with special needs. In the development time, it was then born the idea of inclusive education is friendly public education for all children without exception. In Indonesia, 10 years ago, the Indonesian government has shown the attitude to education for children with special needs to enact legislation governing the national education system and also specifically on inclusive education in Indonesia. But along the way, there are still many schools that still not understand the concept, implementation, and strategies on the implementation of the inclusive education. The purpose of this paper is to explain theconcept, how the implementation and strategies that can be done in the implementation of inclusive education.Keywords : inclusive education, the concept of inclusive education, the implementation of inclusive education, inclusive education strategy